Research on the impact of applying management accounting practices on the operational effectiveness of enterprises in Binh Dinh province - Lê Văn Tân; Đàm Đình Mạnh (My University, 2025)
Research on the impact of applying management accounting practices on the operational effectiveness of enterprises in Binh Dinh province
Keywords: Management accounting; Operational effectiveness; Binh Dinh